Swimming during COVID-19: Operational recommendations and considerations for South African swimming venues - Hill, L.; Nikolaidis, P; Knechtle, B. (South African Journal of Sports Medicine, 2020)
Swimming is one of the most popular recreational activities in South Africa. Since the emergence of the Coronavirus disease 2019 (COVID-19), South Africa imposed one of the strictest lockdown measures to contain and control the spread of the virus. These measures included the closure of gyms, fitness centres and swimming pools across the country. However, as the restrictions begin to ease, it is important to consider how swimming facilities can reopen whilst simultaneously ensuring appropriate measures are in place to reduce COVID-19 infections. Outlined are recommendations and considerations for swimming facilities in South Africa. Currently there is no evidence to suggest that COVID-19 transmission to humans is possible through water, making swimming one of the safer options for physical activity indoors. However, participation is still not without risk and compliance with government mandates and public health officials take precedent over the recommendations outlined in this article.